PENGARUH KEBIJAKAN DIVIDEN, LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Shelita, Fannola; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to determine and empirically prove the effect of dividend policy, liquidity, profitability and firm size on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) with the research period 2017-2019. The sampling method of this research is purposive sampling with a total sample of 73 data obtained from the financial statements of manufacturing companies published by the IDX official website. Data processing in this study was assisted by the SPSS version 25.0 program using the multiple linear regression analysis method. The results showed that partially dividend policy, profitability and firm size had a positive and significant effect on firm value, while liquidity had a negative and insignificant effect on firm value. The results also show that simultaneously dividend policy, liquidity, profitability and firm size have a significant effect on firm value.